Functional brain connectivity and cortical thickness in relation to chronic pain in post-911 veterans and service members with mTBI. (24th August 2018) - Newsome, Mary R.; Wilde, Elisabeth A.; Bigler, Erin D.; Liu, Qisheng; Mayer, Andrew R.; Taylor, Brian A.; Steinberg, Joel L.; Tate, David F.; Abildskov, Tracy J.; Scheibel, Randall S.; Walker, William C.; Levin, Harvey S.
ABSTRACT: Objectives : Investigate the relation of chronic pain interference to functional connectivity (FC) of brain regions and to cortical thickness in post-911 Veterans and Service Members (SMs) who sustained a mild traumatic brain injury (mTBI). Methods : This is an observational study with cross-sectional analyses. A sample of 65 enrollees completing initial evaluation at a single site of the Chronic Effects of Neurotrauma Consortium (CENC) reported pain interference ratings on the TBI QOL. Functional connectivity and cortical thickness were measured. Results : Severity of pain interference was negatively related to FC of the default mode network (DMN), i.e., participants who reported more severe pain interference had less FC between mesial prefrontal cortex and posterior regions of the DMN including posterior cingulate cortex and precuneus. Cortical thickness of specific regions was positively related to severity of pain interference. Conclusion : The more that pain was perceived to interfere with daily life, the less the FC between regions in a network associated with self-referential thought and mind wandering. Although cortical thickness in specific brain regions was positively related to severity of pain interference, follow-up longitudinal data, control group data, and study of individual differences in this cohort will expand this initial report and replicate these findings.